Observando práticas, tecendo conceitos : um estudo sobre as culturas de EJA em Caxias do Sul (1998-2012) - Conrado, Bruna (My University, 2017)
This dissertation, "Observing practices, weaving concepts: a study of the cultures of further education in Caxias do Sul (1998 - 2012)", is the result of a study based on the following research question: what kinds of cultures of further education were constructed in the municipal schools in Caxias do Sul in the period 1998-2012 through an observation of the practices produced through the interaction with the principles of Freire's “generator theme” that were present in the planning and in the narratives of further education teachers? The narrative that was produced aimed to identify the cultures of further education in the municipal schools of Caxias do Sul by interweaving documental sources with the narratives of teachers about their practices, organised from a dialogic methodology using Freire's “generator theme”. In this study, history and culture were understood as elements of everyday life and were based on the concepts of Cultural History, using contributions from Pesavento (2005), Burke (1992), Vidal (2005), Certeau (2012) and Chartier (1990 ) among others. The methodological procedures for the research and the construction of the historical narrative involved documental analysis combined with oral history. A detective approach was adopted in order to explore the material culture within the schools; more specifically the thematic networks that were constructed and organised in the dialogic process inspired by Paulo Freire's works. In addition, particular attention was paid to listening to and reading the narratives of the focus of this dissertation, i.e. the teachers. In this respect, the analysis was guided by an interview with a female teacher, who whilst being an interviewee, also echoed narratives that permeated the analysed documents, and which almost constituted a mouthpiece for other voices. The empirical data and their respective analyses are organised into two aspects: they are firstly presented in thematic networks, taking one of them as an example in order to understand the relationships established therein. Subsequently, the analysis based on the “generated themes” that were raised are presented and there is an attempt to understand some of the impact of the proposals that were implemented during this period through the words of the female teacher that was interviewed. In this part of the study many of the issues identified in the documental analysis combine with the narratives to better illustrate this trajectory. Two categories of analysis emerge: "study as a premise for practice" and "the conflicts and contradictions that exist between theory and practice". From these categories, some results regarding practices and how the research "cultures of further education" are delineated.
A presente dissertação “Observando práticas, tecendo conceitos: um estudo sobre as Culturas de EJA em Caxias do Sul (1998 – 2012)” é fruto de uma investigação que se delineou a partir do seguinte problema de pesquisa: Que Culturas de EJA se constituíram no espaço das Escolas Municipais de Caxias do Sul no período compreendido entre os anos de 1998 a 2012, a partir do rastreamento das práticas produzidas nas vivências dos princípios do Tema Gerador Freireano presentes no planejamento e nas narrativas dos professores da EJA? A narrativa produzida teve como objetivo identificar as culturas de EJA nas Escolas Municipais de Caxias do Sul a partir do entrelaçamento das fontes documentais com as narrativas de seus professores acerca de suas práticas organizadas a partir da Metodologia Dialógica via Tema Gerador Freireano. No estudo, História e cultura foram compreendidas como elementos da vida cotidiana e foram concebidas a partir dos conceitos da História Cultural com as contribuições de Pesavento (2005), Burke (1992), Vidal (2005), Certeau (2012), Chartier (1990) entre outros. Os procedimentos metodológicos para o rastreamento das pistas e para a construção da narrativa histórica envolvem a análise documental combinada com a história oral. Assumiu-se uma atitude detetivesca ao explorar a cultura material das escolas, especificamente as Redes Temáticas construídas e organizadas no processo dialógico inspirado nas produções de Paulo Freire, assim como um olhar atento ao escutar e ler as narrativas daqueles que protagonizaram a história que esta dissertação procurou tematizar: os professores. Neste aspecto, o processo de análise pautou-se na entrevista de uma professora, que enquanto informante, fez ecoar as narrativas que perpassavam os documentos analisados e constitui-se quase que como uma porta-voz de outras vozes. Os dados empíricos construídos e suas respectivas pistas e análises organizam-se em dois aspectos: inicialmente apresentam-se as Redes Temáticas tomando uma delas como exemplo no sentido de compreender as relações que nela se estabelecem. Na sequência, as análises feitas a partir dos Temas Geradores levantados se apresentam. Em um segundo momento abre-se espaço para se tentar compreender algumas marcas deixadas pela proposta implementada no período através das palavras da professora entrevistada. Neste momento, muitas das pistas encontradas no processo de Análise Documental se combinam aos relatos para ilustrar melhor esta trajetória. Duas categorias de análise emergem: “o estudo como premissa para a prática” e “ os embates e contradições vivenciadas entre a teoria e a prática” e, a partir delas, algumas tecituras de que marcas, práticas, ou como a pesquisa vem defendendo, “Culturas de EJA”, são desenhadas.
Keywords: Educação de adultos - Caxias do Sul (RS); Educação - Caxias do Sul (RS); Antropologia educacional; Adult education - Caxias do Sul (Brazil); Education - Caxias do Sul (Brazil); Educational anthropology